Bletilla oligosaccharides improved 5-fluorouracil-induced intestinal mucositis in mice by activating NF-κB signalling pathway and regulating intestinal microbiota - Yin, Qiuxiong; Li, Xinran; Xiong, Yanli; Jiang, Yupeng; Ma, Shengsuo; Qian, Guoqiang (Frontiers in Pharmacology, 2025)
IntroductionThe Bletilla oligosaccharides (BO) are active compounds extracted from Bletilla striata and have the strong protective effect on the gastrointestinal tract. Chemotherapeutic intestinal mucositis (CIM) is one of the toxic side effects of chemotherapeutic agents on the gastrointestinal tract. The aim of this study was to identify the structure of BO and evaluate the therapeutic effect of BO on 5-fluorouracil-induced intestinal mucosal inflammation.MethodsBO were purified from DEAE52 cellulose. The structure of BO were characterised by HPGPC, GC-MS and NMR. In vivo, the mouse model of intestinal mucositis was established by intraperitoneal injection of 5-FU. The effect of BO on intestinal mucositis in mice was detected by assessing the levels of intestinal flora, ZO-1, occludin, and MUC-2, and inflammatory cytokines (IL-1β, IL-6, IL-10, and TNF-α).ResultsStructural characterisation showed that BO were the neutral polysaccharide composed mainly of glucose and mannose. The backbone of BO consisted of→4)-β-Manp-(1→, →4)-β-Glcp-(1→ and small →3,4)-α-Manp-(1→. The results of the in vivo experiment showed that the symptoms of diarrhoea, haematochezia and colonic mucosal lesions improved after administration of BO. Further experiments showed that BO not only reduced the levels of pro-inflammatory factors such as IL-1β, IL-6 and TNF-α, but also improved the expression of intestinal barrier protein and intestinal microbial community after BO treatment.ConclusionBO can relieve the progress of intestinal mucositis by relieving inflammation, protecting the intestinal epithelial barrier and regulating the intestinal microbiota. These data provide experimental evidence for the application of BO in chemotherapeutic intestinal mucositis.